PEMANFAATAN TEPUNG BIJI KORO BENGUK (Mucuna pruriens) SEBAGAI SUBTITUSI TEPUNG KEDELAI PADA PAKAN BENIH IKAN PATIN SIAM (Pangasius hyphopthalmus) - Sherli Veroka; Limin Santoso (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
Catfish (Pangasius hyphothalmus) is one type of freshwater economicalfish that begins developed by fish farmers to cultivation. Catfish are easy to breed,easy maintenance and fast growth. The problem that often be faced in catfishcultivation is the high price of fish diets. One source ingredient used in theformulation of the diet is soybean meal, but the price is relatively expensivebecause of the imported commodity. To reduce dependence on soybean meal, it isnecessary to find an alternative source of local commodity are easily obtained,continuous availability, and have high nutritional value, namely the use velvetbean meal (Mucuna pruriens). The research was aimed to study the utilization ofvelvet bean meal as substitution of soybean meal on diets to the growth of catfishfingerlings. A completely randomized design was five treatments and threereplications. The treatments used applied 0%, 25%, 50%, 75%, 100% velvet beanmeal percentation. Data were analyzed by using ANOVA. The result showeds thattreatment of diet did not give significant influence to the growth of catfishfingerlings. It can be concluded that the velvet bean meal can be used to substitutesoybean meal on diets to the growth of catfish fingerlings from substitution rate of25% to 100%. The best percentage is level substitution 75 % velvet bean meal +25% soybean meal.